2022
DOI: 10.3390/min12050586
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Prospects of Recovering Fine Copper Sulfides from Tailings Using Different Flotation Techniques: A Review

Abstract: Flotation is a common mineral processing method used to upgrade copper sulfide ores; in this method, copper sulfide mineral particles are concentrated in froth, and associated gangue minerals are separated as tailings. However, a significant amount of copper is lost into tailings during the processing; therefore, tailings can be considered secondary resources or future deposits of copper. Particle–bubble collision efficiency and particle–bubble aggregate stability determines the recovery of target particles; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 130 publications
0
3
0
1
Order By: Relevance
“…The challenges encountered in the use of flotation in the recovery of valuable minerals are that the particle sizes of these minerals sent to tailing dams are too fine for conventional flotation. In a review paper by Bilal et al [7], the authors was found the challenges of fine particles' flotation from tailings can be addressed by decreasing the bubble size in the flotation vessel (e.g., the use of column flotation, micro-or nano-bubble flotation) and increasing the particle size approaches (e.g., polymer flocculation, shear flocculation, oil agglomeration, and carrier flotation).…”
Section: Flotationmentioning
confidence: 99%
“…The challenges encountered in the use of flotation in the recovery of valuable minerals are that the particle sizes of these minerals sent to tailing dams are too fine for conventional flotation. In a review paper by Bilal et al [7], the authors was found the challenges of fine particles' flotation from tailings can be addressed by decreasing the bubble size in the flotation vessel (e.g., the use of column flotation, micro-or nano-bubble flotation) and increasing the particle size approaches (e.g., polymer flocculation, shear flocculation, oil agglomeration, and carrier flotation).…”
Section: Flotationmentioning
confidence: 99%
“…Masalah lama yang belum teratasi dengan baik adalah flotasi untuk fine particle (38-13 µm) dan ultrafine particle (<13 µm). Fine particle dan coarse particle terlebih ultrafine particle menghasilkan performa yang buruk bandingkan dengan ukuran menengah [15]. Alasan mengapa hal ini bisa terjadi adalah karena tiga karakteristik fine particle memiliki massa partikel yang rendah.…”
Section: Ukuran Partikel;unclassified
“…α quartz is the dominant mineral in a variety of rock types, including sedimentary, metamorphic, and igneous rocks. 2 The presence of quartz leads to the excessive crushing of the target minerals, resulting in the loss of approximately 10 to 20% of valuable metallic minerals per year 3 and also leads to higher energy consumption for grinding. Separating valuable metallic mineral resources from quartz is a significant challenge due to its sturdy and tough structure that resists crushing and grinding.…”
Section: Introductionmentioning
confidence: 99%